Targeting PD-1/PD-L-1 immune checkpoint inhibition for cancer immunotherapy: success and challenges - Javed, Sadique A.; Najmi, Asim; Ahsan, Waquar; Zoghebi, Khalid (Frontiers in Immunology, 2024)
The programmed death-1 receptor (PD-1) acts as a T-cell brake, and its interaction with ligand-1 (PD-L-1) interferes with signal transduction of the T-cell receptor. This leads to suppression of T-cell survival, proliferation, and activity in the tumor microenvironment resulting in compromised anticancer immunity. PD-1/PD-L-1 interaction blockade shown remarkable clinical success in various cancer immunotherapies. To date, most PD-1/PD-L-1 blockers approved for clinical use are monoclonal antibodies (mAbs); however, their therapeutic use are limited owing to poor clinical responses in a proportion of patients. mAbs also displayed low tumor penetration, steep production costs, and incidences of immune-related side effects. This strongly indicates the importance of developing novel inhibitors as cancer immunotherapeutic agents. Recently, advancements in the small molecule-based inhibitors (SMIs) that directly block the PD-1/PD-L-1 axis gained attention from the scientific community involved in cancer research. SMIs demonstrated certain advantages over mAbs, including longer half-lives, low cost, greater cell penetration, and possibility of oral administration. Currently, several SMIs are in development pipeline as potential therapeutics for cancer immunotherapy. To develop new SMIs, a wide range of structural scaffolds have been explored with excellent outcomes; biphenyl-based scaffolds are most studied. In this review, we analyzed the development of mAbs and SMIs targeting PD-1/PD-L-1 axis for cancer treatment. Altogether, the present review delves into the problems related to mAbs use and a detailed discussion on the development and current status of SMIs. This article may provide a comprehensive guide to medicinal chemists regarding the potential structural scaffolds required for PD-1/PD-L-1 interaction inhibition.